PENGARUH MOTIVASI, METODE PEMBELAJARAN, DAN LINGKUNGAN TERHADAP PRESTASI BELAJAR AKUNTANSI SISWA/I KELAS XI DAN XII ILMU SOSIAL MAN 1 BARABAI - Ferra Maryana; Dewi Normilawati (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research aimed to give empirical evidences about motivation, learning methods and environment to learning achievement. The dependent variable was learning achievement and the independent variables motivation, learning methods and environment. The population in this research was 220 students of XI and XII class of Social Science in MAN 1 Barabai The data collected from the output of questionnaires which give to the respondents. The samples technique used purposive sampling with 69 social science students. The research give empirical evidences that partially only environment which had effect on learning achievement but motivation and learning methods has no effect. Simultaneously, all independent variables had effect on learning achievement.